2017
DOI: 10.5455/medarh.2017.71.107-109
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adolescent Idiopathic Scoliosis on the Occurrence of Varicose Veins on Lower Extremities

Abstract: Introduction:Scoliosis is a complex three-dimensional spine deformity with the frontal plane deflexion (side-shift) of the series of vertebra from the midline and with torque deformity of vertebra, ribs, and the entire trunk towards the apex of curve. Chronic venous diseases present a group of pathological conditions caused by the increased venous pressure. The venous pressure may be increased due to genetics, ligament laxity, general obesity, injuries, and changes in biomechanics of spine and lower extremitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, varicose veins frequently occur in older women [ 30 ]. A previous study reported that female patients with spinal deformities have a higher prevalence of varicose veins [ 31 ]. Therefore, it seems necessary for the analysis to focus on fluid distribution in the lower extremities, such as venous hemodynamics, to explain the difference in phase angle between the IDHS and the controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, varicose veins frequently occur in older women [ 30 ]. A previous study reported that female patients with spinal deformities have a higher prevalence of varicose veins [ 31 ]. Therefore, it seems necessary for the analysis to focus on fluid distribution in the lower extremities, such as venous hemodynamics, to explain the difference in phase angle between the IDHS and the controls.…”
Section: Discussionmentioning
confidence: 99%